The Study of Genius Loci from Rumoh Aceh Perspective at Museum Tsunami Aceh - Ridwan, Nasrullah; Alifa, Yumna; Muftiadi (MAJ - Malaysia Architectural Journal, 2022)
Architecture is a cultural phenomenon that affects and is affected by past events and phenomena. Each place has its own locality and uniqueness that distinguishes it from other places (genius loci). Technological developments should not make architects forget the value of wisdom and identity from a place in their work. Architectural works are realized by continuing cultural values and local traditions, but in harmony with contextual developments with the times so as not to limit creativity. The architecture of the Acehnese house as an identity for the locality of the Acehnese people reflects their religious beliefs, adaptation to nature, and social aspects of society. This study examines the object of the Aceh Tsunami Museum which has a reflection of the values and philosophy of traditional Acehnese house architecture wrapped in a more modern concept in its design. The purpose of this study is to interpret the architecture of the Aceh Tsunami Museum as well as related physical and non-physical elements so that the level of genius loci can be seen from the architecture of Aceh traditional house. The research method used is descriptive-qualitative by presenting the analysis of objects based on the theory of genius loci. The conclusion obtained is that in designing architect tried to translate the essence of local wisdom into design values and principles. However, due to several factors such as the type of building, the function of the building, and other factors, the level of application of the genius loci concept is still very minimal. Meanwhile, architectural elements, visual images, user comfort, memory and fantasy in the museum have an influence on the creation of the spirit of place and atmosphere at the Aceh Tsunami Museum.